Financial and actuarial statistics an introduction - Borowiak Dale S (New York Marcel Dekker, 2003)
Text provides a review of the most recent advances in financial and actuarial modeling, offering a strong statistical background for advanced methods in pension plan structuring, risk estimation, and modeling of investment and options pricing.
Keywords: Actuarial mathematics